Pengembangan Profesionalisme Guru Melalui Pelatihan Karya Tulis Ilmiah - Mispandi; Fahrurrozi , Muh (Al-Madani: Jurnal Pengabdian Pada MAsyarakat, 2024)
The aim of this community service activity is to increase teacher professionalism through scientific work training at SDN 3 Pancor, Selong District, East Lombok Regency with a total of 25 teachers participating. The method used in implementing PKM is using various methods, namely lectures, questions and answers, discussions and evaluation of the results of students' scientific writing. The implementation of PKM can be concluded, among other things: 1) The implementation of scientific writing training for teachers at SDN 3 Pancor has been in accordance with the previously planned stages. 2) Teachers or participants understand the technique of writing scientific papers (KTI) using a scientific paper format that has been prepared by the team so that the activity runs smoothly and well, 3) From the overall response of participants in this Scientific Writing training, they feel very satisfied with the training provided given mainly in relation to the condition of the facilities and infrastructure in the training, mastery of the material by the presenting team, providing opportunities to ask questions, politeness and friendliness of the presenting team, relevance of the training material, systematic delivery of the training material and availability of consumption during the training